High-performance nanostructured SiO2 from Ethiopian pumice: synthesis and characterization - Muhammud, Agraw Mulat; Edossa, Gemechu Deressa; Sabir, Fedlu Kedir (Frontiers in Materials, 2025)
The increasing demand for high-performance, cost-effective nanomaterials has driven significant interest in utilizing natural resources for advanced material production. This study presents the synthesis of nanostructured SiO2 from Ethiopian pumice through a sustainable, environmentally friendly, and cost-effective green chemistry approach. The process involved pumice purification and beneficiation, followed by alkaline leaching and wet sol–gel precipitation, achieved with low energy input and without the need for ablation or post-grinding steps. The end product’s properties were comprehensively analyzed using various techniques, including atomic absorption spectroscopy (AAS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermal analysis (TGA), UV-is spectroscopy, Brunauer–Emmett–Teller (BET) analysis, dynamic light scattering (DLS), scanning electron microscopy (SEM), and energy dispersive X-ray analysis (EDAX). AAS and EDAX analyses confirmed a high purity of 98.52% and an overall yield of 69.07%, within the upper range (50%–75%) reported in the literature, indicating a well-optimized process. BET analysis showed an average pore size of 86.63 nm along with a significant specific surface area of 571.48 m2/g. FTIR identified silanol (Si–OH) and siloxane (Si–O–Si) groups, while XRD revealed an amorphous structure. TGA demonstrated enhanced thermal stability up to 900°C, and UV–Vis analysis verified optical purity. DLS analysis revealed a uniform hydrodynamic diameter distribution within the favorable 10–100 nm range, while SEM images indicated an average primary particle size of 35.83 nm. This study optimized the synthesis of high-purity zero-dimensional (0D) nanostructured SiO2 from Ethiopian pumice, achieving uniform particle size, high surface area, and enhanced stability. The resulting 0D SiO2 outperforms conventional sources in both structural and functional properties, aligning with existing literature and industry standards and positioning it as an ideal and highly effective reinforcement filler for rubber composites. Its versatile properties also support applications in catalysis, adsorption, coatings, and optoelectronics. This work highlights Ethiopian pumice as a sustainable, cost-effective source of advanced silica materials with a strong potential for import substitution in Ethiopia’s tire industry.